Formulasi Nugget Ikan Tongkol dan Tempe Kedelai Sebagai Makanan Selingan untuk Pencegahan Anemia - Latifatul Mukaromah; Fitria Dhenok Palupi; Sugeng iwan Setyobudi (Poltekkes Kemenkes Semarang, 2025)
Background: Anemia is a common health problem among adolescent girls, with a prevalence reaching 42% in East Java. One of the prevention strategies is increasing the intake of foods rich in protein, iron, and vitamins that support hematopoiesis. Skipjack tuna, as a source of heme iron, and tempeh, a fermented soybean product high in iron, have the potential to be developed into nutritious snacks such as nuggets to increase acceptability and consumption among adolescents. Objective: This study aimed to determine the best formulation of skipjack tuna and soybean tempeh nuggets based on nutritional quality and sensory acceptability. Methods: This research employed a Completely Randomized Design (CRD) with three skipjack tuna: tempeh ratios: P1 (100:30), P2 (100:50), and P3 (100:70). A hedonic test was conducted involving 25 semi-trained panelists. Data analysis used the Kruskal–Wallis test followed by the Mann–Whitney post-hoc test. Nutrient composition was calculated using TKPI and Nutricheck. Results: The resulting nuggets were characterized by a slightly bitter taste, golden-yellow color, slightly beany aroma, and chewy texture. The nutritional content per 100 g ranged from 467.52–494.32 kcal energy, 16.80–19.57 g protein, 20.41–21.58 g fat, 55.59–57.39 g carbohydrates, and 3.34–3.87 mg iron. The best formulation was P1, with the highest total score (0.644), an iron content of 1.67 mg per serving, and the highest taste acceptability. Conclusion: The best formulated nuggets meet (P1) the recommended nutrient intake for adolescent girls aged 13–15 years, contributing approximately 10% of the daily requirement based on the 2019 Recommended Dietary Allowances (RDA).